STRATEGI PEMASARAN PROGRAM STUDI DIPLOMA III USAHA PERJALANAN WISATA UNIVERSITAS JEMBER - Nugroho, Margaretta Andini; Darma Putra, I Nyoman (Jurnal Master Pariwisata (JUMPA); Volume 04, Nomor 01, Juli 2017DO - 10.24843/JUMPA.2017.v04.i01.p04, 2017)
A marketing strategy is needed by Program Studi Diploma III Usaha Perjalanan Wisata (PS D-III UPW) of Jember University, in order to increase more students. Since the last few years, the students of PS D-III UPW has been decreased. This study has the objective to identify strengths, weaknesses, opportunities and threats of PS D-III UPW, and formulate the marketing strategy, by using analysis method of IFAS, EFAS, SWOT and QSPM. The result of IFAS and EFAS identify that PS D-III UPW has 16 factors of strength, 14 factors of weakness, 6 factors of opportunity and 3 factors of threat. The result of SWOT identifies some alternative strategies, which are technology information, student motivation, cooperation within tourism industry, promotion, facilities, competitive product, learning system, quality of human resource, and involvement of the students at Jember tourism events. The QSPM identifies that improvement of promotion as the first priority strategy.